NON-CONTACT PHOTOGRAMMETRIC METHODOLOGY TO EVALUATE THE STRUCTURAL HEALTH OF HISTORICAL CONSTRUCTIONS - L. J. Sánchez-Aparicio; A. Villarino; J. García-Gago; D. González-Aguilera (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
Accurate studies of cultural heritage structures usually require the application of combined techniques to understand its structural behaviour. It is in this context, where the article present a set of procedures based on the dual combination of photogrammetric methodologies (image-based modelling and digital image correlation) and the finite element method to understand the structural behaviour of these structures. Through the interpretation of the different obtained products, by the defined approach, it is possible to estimate and evaluate the causes of the structural damage that the analysed infrastructure can suffer and also design subsequent restoration mechanisms, always from a perspective of minimal intrusion to the structure. This case of study aims to validate the methodology presented, using as an example a case of vernacular architecture (a dome) in Sejas de Aliste (Zamora, Spain).